Bevacizumab and Glioblastoma: Past, Present, and Future Directions. Issue 4 (July 2018) - Kim, Michelle M.; Umemura, Yoshie; Leung, Denise
Abstract : Abstract: Glioblastoma (GBM) is the most common and lethal intracranial malignancy, with few advances in treatment over the last several decades. Much excitement surrounded the initial approval for bevacizumab for recurrent GBM, given the marked radiographic responses and improvement in progression-free survival observed in early studies. However, phase III studies have failed to demonstrate an overall survival advantage with the use of this agent. An overview of the mechanism of action and activity of bevacizumab in adult gliomas, a timeline of pivotal clinical trials, data on its impact on quality of life and imaging, and its role in managing the sequelae of treatment provide evidence for its current use. Investigations into combinatorial approaches utilizing bevacizumab with reirradiation and immunotherapy and ongoing work to identify biomarkers to select patient subsets who may benefit from treatment elucidate important unanswered questions that will further define the role of bevacizumab in the management of patients with GBM.